Recurrent patellar dislocation: treatments and challenges - Yang, Fei; Chen, Changshun; Chen, Rongjin; Yang, Chenhui; Xiao, Hefang; Feng, Zhiwei; Geng, Bin; Xia, Yayi (Frontiers in Surgery, 2025)
Recurrent Patellar Dislocation (RPD) is a common knee sports injury, mainly affecting pediatric and adolescent populations, posing a significant challenge in orthopedic clinical practice. Although a variety of treatments have been reported, and many of them have shown good initial results, there is a lack of long-term follow-up results. Each treatment method has its own unique characteristics and limitations, and there is no standardized and unified treatment plan. This article provides a comprehensive review of current treatments for RPD. We believe that regardless of the surgical method used, patellar dislocation should not occur at 0°–90° of postoperative knee flexion and extension, and the range of motion should not be limited. Our ultimate goal is to restore patellar stability and improve lower limb alignment, thereby restoring knee function as much as possible. In addition, future treatment options for RPD are also discussed. In the future, there should be more in-depth research on the risk factors and pathogenesis that lead to recurrent patellar dislocation, as well as more randomized controlled trials focusing on different treatment methods. A comprehensive understanding of these is crucial for implementing preventive measures and developing targeted treatment strategies. The goal of this narrative review is to offer clinicians a deeper understanding of RPD treatment, enhance clinical decision-making skills, and encourage personalized and efficient management of RPD treatment.